2020
DOI: 10.1186/s12884-020-03106-4
|View full text |Cite
|
Sign up to set email alerts
|

Maternal childbirth experience in induced and spontaneous labour measured in a visual analog scale and the factors influencing it; a two-year cohort study

Abstract: Background Poor maternal childbirth experience plays a role in family planning and subsequent pregnancies. The aim of this study was to compare childbirth experiences in induced and spontaneous labor and to investigate the factors influencing the childbirth experience. Methods This two-year cohort study included all women with term singleton pregnancies in cephalic presentation aiming for vaginal delivery at Helsinki University Hospital between January 2017 and December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 21 publications
11
47
0
Order By: Relevance
“…Factors associated with a worse patient satisfaction are caesarian delivery (OR : 0,31 [0,17 -0,54]) and the occurrence of postpartum hemorrhage [OR 1.3 (95% CI 1.1-1.6)] which is also in agreement with previous studies 14,26 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Factors associated with a worse patient satisfaction are caesarian delivery (OR : 0,31 [0,17 -0,54]) and the occurrence of postpartum hemorrhage [OR 1.3 (95% CI 1.1-1.6)] which is also in agreement with previous studies 14,26 .…”
Section: Discussionsupporting
confidence: 91%
“…Factors associated with patient satisfaction according to our study were concordant with previous studies 14,26 : primiparity, delivery within 24 hours after start of labour induction and the quality of the received information.…”
Section: Discussionsupporting
confidence: 90%
“…In line with previous research, the women in our cohort with negative childbirth experience were more likely to be primiparous, have induced labor, an infant with Apgar score < 7 at 5 minutes, oxytocin augmentation, operative vaginal birth or emergency CS, obstetric anal sphincter injury or postpartum hemorrhage 2,3,13 .…”
Section: Discussionsupporting
confidence: 89%
“…Maternal childbirth experience is affected by several factors including maternal age, mode of delivery, postpartum hemorrhage, low Apgar score, induction of labor and obstetric anal sphincter injury 2,3,6,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Some previous reports have shown that women may be less satisfied with their care or experience of labor if their labor is induced 24‐27 . This highlights the importance of information, support and counseling during IOL, especially in OP care.…”
Section: Discussionmentioning
confidence: 92%